Molecular characterization, spatiotemporal expression patterns of fatty acid elongase (elovl8) gene, and its transcription changes in response to different diet stimuli in yellow catfish (Pelteobagrus fulvidraco) - Zeng, Wan-Hong; Wei, Xiu-Ying; Qin, Wei; Qin, Chuan-Jie; Shi, Qiong; Guo, Sheng-Tao; Prathomya, Panita; Zhang, Shi-Yong; Fu, Peng; Hu, Wei; Yuan, Han-Wen; Wen, Zheng-Yong (Frontiers in Marine Science, 2023)
Elongase of very long-chain fatty acid 8 (Elovl8) is a new member identified in the Elovl family that is involved in the synthesis of highly unsaturated fatty acids (HUFAs). However, the evolutionary and physiological roles of this enzyme are still largely unknown. In the present study, the elovl8 gene was identified and characterized from yellow catfish Pelteobagrus fulvidraco, and then its evolutionary and molecular characteristics as well as transcriptional changes in response to various nutritional status were determined. Results showed that the open reading frame (ORF) of elovl8 was 795 bp in length, encoding a protein of 264 amino acids. Multiple sequences alignment showed that the yellow catfish Elovl8 was highly conserved with other homologs in teleosts, sharing similar structural characteristics (including six conserved transmembrane α-helical domains, four conserved elongase motifs, and three highly conserved cysteine residues). Meanwhile, comparisons of genetic synteny confirmed that the elovl8 gene identified from the yellow catfish was the homolog of elovl8b in other teleosts, and thus, the elovl8a gene was lost in the genome of the yellow catfish. Gene structure analysis revealed that the elovl8b gene contained eight exons and seven introns, which was highly conserved in teleosts, implying the functional conservation among various fish species. Tissue distribution analysis detected by real-time quantitative PCR (RT-qPCR) showed that the elovl8 gene was extensively expressed in all detected tissues except eyes, with high expression levels in the intestine and liver. Temporal expression analysis revealed that the expression level of elovl8 was stably expressed in the early 12 h after fertilization, and then dramatically decreased at 24, 48, 72, and 96 h after fertilization, implying that elovl8 is required for HUFA biosynthesis in the early development stages. Functional experiments showed that the expression of the elovl8 gene was stimulated after feeding with egg yolk but was not obviously affected after feeding with halogenated worms, indicating that diets full of HUFAs can inhibit the expression of elovl8 in yellow catfish. Our findings will help us to better understand the evolutionary and functional characteristics of elovl8 in teleosts, and lay a solid basis for investigating the regulation mechanism of HUFA biosynthesis.